A trajetória da linguagem cênica no CEFET-MG - Maia, Cícera Vanessa (2010)
This study aimed to understand the experiences of students in classes for the Performing Arts at CEFET-MG so that try to establish the parallel between the created characters from the scenic laboratories, mirror exercises, integrating them until the final scene elaborated by them in the classroom. It is a collaborative research (auto) biographical, ie the life narratives and oral and written reports that traces the history and retrieve past events, reflective observation made by means of systematic and cyclical processes of reflection in and on action. To collect the information were carried out three questionnaires during the school year. A major objective would be to understand why the characters are archetypes fulfill the scenes of anti-heroes created by students from their own images reflected in the mirror. The student understands that this young hero and antihero in building their own identity? How effective is the way to look, see, realize feel, think, create, recognize, develop and then represent the character. The text is collective production of several characters. At the time of construction of the spectacle, after experiencing what each brought to the scene the students in an effort to become effective team in the rite of passage that makes up the scenario. The main outcome of the stage production where the stories and actors mingle and meet represented by heroes of everyday life, an example of men on stage